ANALYSIS RESULTS OF MONITORING AND EVALUATION CONTINGENT EAST JAVA ON NATIONAL SPORTS XIX WEST JAVA - Hantoro, Budi (LPPM Universitas Kahuripan Kediri, 2019)
Training for athletes should have been undertaken in continuous and sustainable and begins as early as possible since individual show a wish in the field of sports , and should be implemented with coached the talent and sports achievement. Talk about national event as national sports week (PON), contingent east java was also experienced all that are similar to the state of indonesia which are not there is an increase of achievement. This could could be seen from the results of rank east java contingent on the operation of PON XVII contingent east java managed to become the top winner, but achievement that could not be maintained at PON XVIII in Pekanbaru Riau. Hence hub ahead of national sports XIX 2016 in Bandung west java contingent east java not wanted to experience something similar with the results of previous pound, contingent east java want to win back and repeating the successful at PON XV 2000 and PON XVII 2008 who ranks one a winner.